Community initiatives as a catalyst for regeneration of heritage sites: Vernacular transformation and its influence on the formal adaptive reuse practice. (August 2018) - Plevoets, Bie; Sowińska-Heim, Julia
Abstract: Over the past few decades, the adaptive reuse of buildings—transforming them to meet new functional and aesthetic needs and requirements—has become a highly specialized domain within architectural and conservation practice, and is becoming a field of scholarly study in its own right. However, in juxtaposition with this highly specialized practice, people reuse and adapt all sorts of buildings in spontaneous and informal ways in a process we call "vernacular adaptation." This paper investigates such vernacular adaptation of built heritage, along with its specific characteristics, opportunities, and threats as well as its influence on more formal adaptive reuse practice. As methodology, we examine relevant literature to review historical and contemporary examples of vernacular adaptation and reuse. In conclusion, we present the vernacular approach as a valuable alternative to the "formal" or specialized, top-down method to managing existing built environment, especially for buildings and sites that possess compelling social value. Moreover, our study indicates that in practice, the division between the vernacular and the formal is not rigid, elaborating on the possibilities and risks of joined initiatives between local communities and private or public developers. Highlights: A bottom-up, user-led practice – the vernacular reuse – towards adaptive reuse has existed during all periods Vernacular adaptive reuse is a valuable alternative to the formal practice of dealing with the build environment The vernacular and formal practice are often intertwined and contribute to one-another